ANALISIS DAYA DUKUNG WISATA DAN PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN WISATA BAHARI PANTAI TORONIPA - Gerry Septian Nugraha; Anas Nikoyan; Muh. Ramli (Universitas Halu Oleo, 2020)
The problems and objectives studied in the study were to analyze the effective carrying capacity of Eucalyptus Tourism (ECC) of Toronipa Beach according to landscape aspects, area and number of tourists; the form and level of community participation in the development of Toronipa Beach marine tourism; and the development of Toronipa Beach marine tourism to advance tourism and be more valuable and competitive. This study uses a quantitative and qualitative approach using survey design. The sample in the study were 27 people purposively. Data were analyzed quantiatively and descriptively quality. The results of the study concluded that the tourism carrying capacity (ECC) of Toronipa Beach was 25,592 people per day, or around 8,531 people every 3 hours. Community participation in the development of Toronipa Beach marine tourism is